Pornography as a cultural resource for constructing and expressing gendered sexual subjectivities among students in a co-educational boarding school. Issue 2 (3rd April 2022) - Setty, Emily
ABSTRACT: This paper draws upon research conducted in a co-educational independent boarding school in England to explore the role of pornography in students' school-based sexual cultures. Drawing upon Mechling's conceptualization of boarding schools as 'total institutions', I explore how pornography acted as both 'play' and 'ritual' through which participants asserted agency and control while producing a gendered social order surrounding sex and sexuality. Participants who spoke about pornography drew upon dominant understandings of masculine and feminine (hetero)sexuality when positioning themselves and one another regarding pornography. They tended to construct viewing pornography as a 'typical' and 'normal' part of masculine (hetero)sexuality but as antithetical to feminine (hetero)sexuality. Some of the boys expressed ambivalence and uncertainty about pornography, but this was often grounded in taken-for-granted gendered constructs about sexual performance and accomplishment. Socially approved expressions of agency and control within the research environment were, therefore, both reflective and constitutive of a gendered and heteronormative social order. I suggest that sex education should attend to the role that pornography plays as a cultural resource through which young people construct, express and designate gendered sexual subjectivities and social roles.